AKT2 siRNA delivery with amphiphilic-based polymeric micelles show efficacy against cancer stem cells. (1st January 2018) - Rafael, Diana; Gener, Petra; Andrade, Fernanda; Seras-Franzoso, Joaquin; Montero, Sara; Fernández, Yolanda; Hidalgo, Manuel; Arango, Diego; Sayós, Joan; Florindo, Helena F.; Abasolo, Ibane; Schwartz, Simó; et al.
Abstract: Development of RNA interference-based therapies with appropriate therapeutic window remains a challenge for advanced cancers. Because cancer stem cells (CSC) are responsible of sustaining the metastatic spread of the disease to distal organs and the progressive gain of resistance of advanced cancers, new anticancer therapies should be validated specifically for this subpopulation of cells. A new amphihilic-based gene delivery system that combines Pluronic ® F127 micelles with polyplexes spontaneously formed by electrostatic interaction between anionic siRNA and cationic polyethylenimine (PEI) 10K, was designed (PM). Resultant PM gather the requirements for an efficient and safe transport of siRNA in terms of its physicochemical characteristics, internalization capacity, toxicity profile and silencing efficacy. PM were loaded with a siRNA against AKT2, an important oncogene involved in breast cancer tumorigenesis, with a special role in CSC malignancy. Efficacy of siAKT2-PM was validated in CSC isolated from two breast cancer cell lines: MCF-7 and Triple Negative MDA-MB-231 corresponding to an aggressive subtype of breast cancer. In both cases, we observed significant reduction on cell invasion capacity and strong inhibition of mammosphere formation after treatment. These results prompt AKT2 inhibition as a powerful therapeutic target against CSC and pave the way to the appearance of more effective nanomedicine-based gene therapies aimed to prevent CSC-related tumor recurrence.